2015
DOI: 10.1007/s00535-015-1081-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastric atrophy and xanthelasma are markers for predicting the development of early gastric cancer

Abstract: Gastric xanthelasma is a useful marker for predicting the development of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 32 publications
1
58
0
Order By: Relevance
“…Sekikawa et al [26,27] revealed that the prevalence of gastric xanthomas (“xanthelasma” in the original manuscripts) is significantly higher in patients with gastric cancer (47.6-51.7%) and they found that gastric xanthomas were independent factors related to gastric cancer. In multivariate analysis, the odds ratio of gastric xanthomas for developing gastric cancer was 6.38, which was significantly higher compared to open-type atrophy (7.37), male (2.60), and age ≥65 (1.59) [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sekikawa et al [26,27] revealed that the prevalence of gastric xanthomas (“xanthelasma” in the original manuscripts) is significantly higher in patients with gastric cancer (47.6-51.7%) and they found that gastric xanthomas were independent factors related to gastric cancer. In multivariate analysis, the odds ratio of gastric xanthomas for developing gastric cancer was 6.38, which was significantly higher compared to open-type atrophy (7.37), male (2.60), and age ≥65 (1.59) [26].…”
Section: Discussionmentioning
confidence: 99%
“…1, 2) once it has developed. There have been some studies investigating the relationship between gastric xanthomas and cancer [26,27], however, it still remains unclear how gastric xanthomas are involved in the development of gastric cancer. In this study, we investigated the clinicopathological features of gastric cancer with or without xanthomas in detail using a database of a high-volume center treating over 200 cases of gastric cancer per year.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, we did not obtain any data on plasma insulin and c-peptide, and the number of patients who developed early gastric cancer was small. However, our study demonstrated unequivocally that the presence of DM was significantly related to the development of early gastric cancer in patients with gastric xanthelasma.Naturally, it is very important to examine the presence of Helicobacter pylori infection and to evaluate the severity of gastric atrophy in order to predict the development of early gastric cancer in patients undergoing endoscopic examination [1,5]. However, our data additionally demonstrate that xanthelasma may also be a useful predictive marker for the development of early gastric cancer.…”
mentioning
confidence: 54%
“…Naturally, it is very important to examine the presence of Helicobacter pylori infection and to evaluate the severity of gastric atrophy in order to predict the development of early gastric cancer in patients undergoing endoscopic examination [1,5]. However, our data additionally demonstrate that xanthelasma may also be a useful predictive marker for the development of early gastric cancer.…”
mentioning
confidence: 54%
See 1 more Smart Citation